Effectiveness of Social Science Learning Based on Noble Values of Ki Hajar Dewantaras Teaching to Strengthen the Students Character - Warsito, Warsito; Asrowi, Asrowi (International Journal of Active Learning, 2017)
The objectives of this research are: 1) to describe the reasons why social science learning based on the noble values of Ki Hajar Dewantaras teaching is effective to strengthen the students character; 2) to describe the effectiveness of social science learning based on the noble values of Ki Hajar Dewantaras teaching in to strengthen the students character; 3) to compare the effectiveness of the enhancement of the students character of social science learning through the noble values of Ki Hajar Dewantaras teaching and conventional social science learning. This research used the mixed methods. The population was the students in Grade VIII of State Junior Secondary Schools in Solo Raya and its vicinity which encompasses Surakarta City, Boyolali Regency, Sukoharjo, Karanganyar, Wonogiri, Sragen, and Klaten. The data were collected through (1) test, (2) questionnaire, (3) in-depth interview, (4) observation, and (5) documentation. The data were analyzed by using the difference test. The results of research are as follows: 1) the reasons why social science learning process based on the noble values of Ki Hajar Dewantaras teaching is effective to strengthen the students character 2) Social science learning based on the noble values of Ki Hajar Dewantaras teaching is more effective in strengthen the students understanding of character education, and it is more effective than the conventional learning as indicated by the results of the difference test.